History, memory, performance - Dean, D. M. (David M.); Meerzon, Yana; Prince, Kathryn 1973- (Studies in international performance, 2015)
"History, Memory, Performance is an interdisciplinary collection of essays exploring performances of the past in a wide range of trans-national and historical contexts ranging from seventeenth century New France and nineteenth-century Russia to modern Australia, Brazil, Britain, Canada, Lebanon, Russia, and the United States. Contributions from theatre scholars and public historians address issues of shared interest to the disciplines of theatre studies and theatre history, performance studies, history, and public history, coalescing around the concept of memory, both collective and individual. Wide-ranging and theoretically engaged, History, Memory, Performance is especially timely given the historical turn in theatre studies and the performative turn in historical studies. "--